Detection of HIV p17 antigen in lymphocytes but not epithelial cells from cervicovaginal secretions of women seropositive for HIV: implications for heterosexual transmission of the virus. Issue 1 (February 1988) - Van de Perre, P; De Clercq, A; Cogniaux-Leclerc, J; Nzaramba, D; Butzler, J P; Sprecher-Goldberger, S
Abstract : Human immunodeficiency virus (HIV) has been isolated from cervicovaginal secretions from infected women and is thought to be cell associated. To identify which cells harbour viral antigen, we used monoclonal antibodies to OKT4 and a monoclonal antibody directed against HIV p17 core antigen to perform indirect immunofluorescence assays of genital secretions from 17 HIV seropositive and 17 HIV seronegative women with leucorrhoea. OKT4 positive lymphocytes were detected in all tested samples. HIV p17 antigen was detected in the genital fluid lymphocytes in nine out of 14 seropositive subjects from whom lymphocytes were available. No viral antigen was detected in genital fluid lymphocytes of seronegative subjects, nor in any cervicovaginal epithelial cells. This study shows that lymphocytes are the major source of HIV in cervicovaginal secretions of infected women. Conditions that increase the lymphocyte population in the female genital tract, such as sexually transmitted disease (STD), chronic inflammation of the cervix, and menstruation, may facilitate the transmission of HIV during sexual intercourse.